Modernisasi teknologi pendidikan Islam di wilayah nusantara - Fathurrohman, Rafif Agil; Syafi’i, Imam; Ghozi, Ahmad; Izzanugraha, Ahsan Latif (Maliki Interdisciplinary Journal, 2024)
This article discusses the renewal of technology in the education system in the context of Islam and culture, focusing on the impact of technology on the system in the digital era. The use of information technology has led to advances in learning techniques, although the impact varies based on how it is used properly. This research uses the literature method, looking at related literature to understand the basics of technological development in the context of Islam and culture. Educational reform intends to change the learning system using innovations that make students have holistic thinking. Technology not only helps in the teaching and learning process but also increases effectiveness and efficiency for teachers. This article also discusses the important role of education for the advancement of society and the importance of improving the education system to keep pace with developments in the digital era. Indonesian laws and regulations that present religious education in the country’s education system as national education, to ensure that the audience of the education system gets an inclusive education that can meet the needs of students.